VISUAL ANALYSIS AND GENERATION Z’S INTEREST IN YOU-C 1000 ADVERTISING VIDEO - Hutami, Anindya Pradipta; Amelia, Sani Ratna; Maulviyah, Nerissa Nadhrota; Mashudi, Achmad Ibrahim; Dewi, Putu Chrisma; Susanto, Putu Chris (Seminar Ilmiah Nasional Teknologi, Sains, dan Sosial Humaniora (SINTESA), 2022)
ABSTRACT Entering 2020, one of the trends that marketers should pay attention to is the growing influence of Generation Z. The new generation that will dominate the market after the millennial segment is Generation Z. Video is believed to be a medium that is quite influential in building bonds with the audience. This study aims to analyze the use of video visual media in increasing Generation Z’s interest in the products offered and to understand Generation Z’s level of interest in video advertising as a visual medium. The method used in this action is a qualitative grounded theory model that analyzes abstract theories about processes, actions, or interactions based on the views of participants. In addition, it also uses the SWOT analysis method which is used to monitor and evaluate research conducted both from external and internal factors for a particular purpose. In this study there are two stages, the first is the interview stage to determine the response of Generation Z participants who tend to be interested in the visualization of advertisements for the You-C 1000 Vitamin Drink product. Then in the second stage, namely analyzing the results of the interview to find out the participant’s response to the product ad video. The results showed that the visual video media succeeded in increasing the interest of participants from Generation Z to watch advertisements until they ran out. Keywords: Generation Z, Interest, Advertising, Video, Grounded theory